Precautionary reserves and the interbank market - Adam Ashcraft; James McAndrews; David Skeie (Federal Reserve Bank of New York, 2009)
Liquidity hoarding by banks and extreme volatility of the fed funds rate have been widely seen as severely disrupting the interbank market and the broader financial system during the 2007-08 financial crisis. Using data on intraday account balances held by banks at the Federal Reserve and Fedwire interbank transactions to estimate all overnight fed funds trades, we present empirical evidence on banks' precautionary hoarding of reserves, their reluctance to lend, and extreme fed funds rate volatility. We develop a model with credit and liquidity frictions in the interbank market consistent with the empirical results. Our theoretical results show that banks rationally hold excess reserves intraday and overnight as a precautionary measure against liquidity shocks. Moreover, the intraday fed funds rate can spike above the discount rate and crash to near zero. Apparent anomalies during the financial crisis may be seen as stark but natural outcomes of our model of the interbank market. The model also provides a unified explanation for several stylized facts and makes new predictions for the interbank market.
Keywords: G21; G10; E40; D53; 330; Excess reserves; fed funds rate; hoarding; liquidity; limited participation; payments